(untitled) (GnosisWisdom, 2023)
Objective To characterize the clinical epidemiological behavior of nutritional deficiency in groups of greater susceptibility in attended in the Provider Institutions of Health Services-IPRESS of first level of attention in the region of Huancavelica. Materials and methods. Type of descriptive study, descriptive level, non-experimental design, descriptive transactional, scientific method and documentary analysis. The population and sample consisted of children and pregnant women, the documentary analysis technique and documentary content analysis sheet were used. Results. 20.3% and 19.3% (2020 and 2021) of children under 5 years of age with mild anemia, 12.4% and 11.1%; present moderate anemia and 0.4% and 0.3%; severe anemia; respectively; 5.0% and 4.8%; with global malnutrition; 5.0% and 4.7%; overweight, 1.4% and 1.1%; obesity; 1.3% and 1.4%, with acute malnutrition; 27.8% and 23.8%; with chronic malnutrition. 16.0% and 15.3% of pregnant women with mild anemia, 17.7% and 16.0%; present moderate anemia and 0.8% and 0.7%; severe anemia; respectively and 35.5% and 29.6%; overweight, 25.5% and 7.0%; they present deficit; respectively. Conclusions. Population groups considered most vulnerable; children and pregnant women still have nutritional deficiencies such as anemia and malnutrition (malnutrition).